2016
DOI: 10.1111/jdv.13808
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tofacitinib withdrawal and re‐treatment on patient‐reported outcomes: results from a Phase 3 study in patients with moderate to severe chronic plaque psoriasis

Abstract: BackgroundTofacitinib is an oral Janus kinase inhibitor being investigated for psoriasis. A Phase 3 withdrawal/re‐treatment study (NCT01186744; OPT Retreatment) showed tofacitinib re‐treatment was effective in patients with chronic plaque psoriasis.ObjectivesTo describe the effects of tofacitinib withdrawal/re‐treatment on health‐related quality of life (HRQoL) and disease symptoms measured by patient‐reported outcomes (PROs).MethodsThe study was divided into initial treatment, treatment withdrawal, and re‐tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…In sum, this study indicated that tofacitinib could be efficacious after withdrawal and retreatment. 30,31 OPT Compare was a randomized, placebo-controlled, 12 week, non-inferiority phase III trial comparing tofacitinib 5 mg and 10 mg to high dose entanercept or placebo in patients with moderate-to-severe plaque psoriasis. The primary endpoints were the proportion of patients with a PASI75 and the proportion of patients with a PGA response at 12 weeks of treatment.…”
Section: Psoriasis Clinical Trialsmentioning
confidence: 99%
“…In sum, this study indicated that tofacitinib could be efficacious after withdrawal and retreatment. 30,31 OPT Compare was a randomized, placebo-controlled, 12 week, non-inferiority phase III trial comparing tofacitinib 5 mg and 10 mg to high dose entanercept or placebo in patients with moderate-to-severe plaque psoriasis. The primary endpoints were the proportion of patients with a PASI75 and the proportion of patients with a PGA response at 12 weeks of treatment.…”
Section: Psoriasis Clinical Trialsmentioning
confidence: 99%
“…The combination of tofacitinib 5 mg, BID with MTX, as approved for the treatment of RA, could also be a future option in the management of plaque psoriasis, especially if associated with PsA. In the Pivotal Retreatment study no rebound phenomena have been experienced [18], however it is not fully clear if tofacitninib can produce rebound phenomena upon withdrawal as reported for CsA. Similar to CsA the effect on T cell suppression is strong but rapidly reversible.…”
Section: Expert-commentary/discussionmentioning
confidence: 99%
“…The efficacy of tofacitinib in reducing pruritus based on ISI score in patients with psoriasis has previously been reported (34)(35)(36). Placebo-adjusted mean decreases from baseline ISI scores surpassed the CID determined in this analysis (1.48), at ≤ 2 weeks with both tofacitinib doses in OPT Pivotal 1 (-1.48 at Day 13 and -1.55 at Day 6 for tofacitinib 5 and 10 mg BID, respectively), and with tofacitinib 10 mg BID in OPT Pivotal 2 (-1.56 at Day 11) and OPT Compare (-1.57 at Day 9), indicating clinically relevant improvements in pruritus with tofacitinib.…”
Section: Clinically Meaningful Improvements In Itch Severity Item Scomentioning
confidence: 99%
“…The efficacy and safety of tofacitinib has also been studied in several immunemediated inflammatory diseases, including rheumatoid arthritis (16)(17)(18)(19)(20)(21), psoriatic arthritis (22)(23)(24), ankylosing spondylitis (25), Crohn's disease (26)(27)(28), and ulcerative colitis (29,30). Moreover, the impact of tofacitinib on pruritus has previously been reported in Phase 2 studies of tofacitinib as a topical treatment for atopic dermatitis (31) and psoriasis (32), and Phase 2 and 3 studies of tofacitinib as an oral treatment for psoriasis (33)(34)(35)(36).…”
mentioning
confidence: 99%
See 1 more Smart Citation